Biological Activities of Barringtonia Racemosa (Lecythidaceae) and the Quantitative Analysis of Phenolic Acids And Flavonoids Present in the Various Bioactive Extracts of the Species - Hussin, Nurul Mariam (2009)
Barringtonia racemosa (Family Lecythidaceae) posses several bioactivities and is used in traditional medicine of Malaysia. However, its antioxidant, antimicrobial, anti-inflammatory and allelopathic activities investigation are still lacking. The aims of this study were therefore to determine those biological activities of methanolic, ethanolic and hot water leaf, stem and bark extracts of B. racemosa and quantitative analysis of phenolic acids and flavonoids present in the various bioactive extracts of the species. The methanolic and ethanolic extracts of bark showed strong free radical scavenging activity (89.23 ± 0.40 and 91.35 ± 0.89 %) and this was even higher than butylated hydroxytoluene (BHT), ascorbic acid and α-tocopherol (antioxidant standards). The results also showed that all methanolic extracts (leaf, stem, and bark; 84.47 ± 0.05, 84.41 ± 0.28 and 84.03 ± 0.03 %) and ethanolic extracts of leaf and bark (82.58 ± 0.06 and 88.21 ± 0.06 %), respectively had similarly strong reducing power when compared to the antioxidant standards, tested in this study. The leaf of methanolic and ethanolic extracts showed strong antioxidant activity (80.03 ± 5.56 and 88.93 ± 8.32 %) in the β-carotene bleaching assay which were higher than the antioxidant standards. Although most of the hot water extracts showed weak to moderately antioxidant activities, the hot water extract of the leaf surprisingly showed strong reducing power potential (83.45 ± 0.07 %). Overall, the methanolic and ethanolic extracts of B. racemosa had effective antioxidant activities compared to hot water extracts. In Griess assay, all the B. racemosa extracts showed no significant activity on nitric oxide inhibition in RAW264.7 cell line. However, the extracts do not seem to be cytotoxic. In antibacterial assay, B. racemosa aerial parts extracts showed weak to moderate inhibitory activities against both Gram-positive and Gram-negative bacteria tested accept for boiling water extracts which was inactive. For antifungal assay, methanolic extracts of B. racemosa leaf, stem and bark exhibited the higher inhibitory activity among the four of seven fungi tested. Among different fungi tested, all extracts were found to be more sensitive to Fusarium sp. compared to the others. The seed germination assay results showed that B. racemosa extracts were able to effect the germination of the Brassica nigra L. (allelopathic activity). In the present study, quantitative analysis of phenolic compounds from B. racemosa leaf, stem and bark were performed using reversed-phase high performance liquid chromatography (RP-HPLC) technique. The results showed that gallic acid and naringin were the major phenolic acids and flavonoids present in all different aerial parts of B. racemosa. Ferulic acid, rutin, kaempferol and luteolin were also detected in several aerial parts of B. racemosa. Overall results obtained from the biological assays suggested that B. racemosa is a source of bioactive compounds endowed with interesting biological activities, such as strongly antioxidants agents and can be rated as good dietary sources of natural phenolic antioxidants.